The Understanding of cash waqf among students of accounting, semester 2, Faculty of Accounting, UiTM Puncak Alam / Mohammad Dinniey Zikriey Nordin - Nordin, Mohammad Dinniey Zikriey (2019)
A study on the understanding of cash waqf among student. The total number of student involved is 300 people (population). The method that has been used are quantitative that is a questionnaire through the google form and qualitative which is library research as the second method. The result showed that the student of Accounting had a moderate level of understanding of cash waqf concept on the objectives of the study. In conclusion, the emphasize towards student about cash waqf are important and need to take serious so that it will ease people to perform worship perfectly.